2019
DOI: 10.7224/1537-2073.2018-027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Anxiety and Cognition in Multiple Sclerosis

Abstract: Background: Anxiety, which is very prevalent in multiple sclerosis (MS) but understudied, has been shown to negatively affect cognition in many different populations. Slowed information processing speed underlies most cognitive impairments in MS, including verbal learning. The aim of this study was to look at how anxiety influences cognition—specifically processing speed and verbal learning—in MS. Methods: Eligibility criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Notably, anxiety-state scores, in combination with other biomarkers, also contributed to a prediction of neuropsychological performance in our patient cohort, highlighting the significant effect of anxiety symptoms on cognition in patients with MS. 32 These findings are not surprising given that high prevalence rates of psychiatric comorbidity 33 have been well documented in patients with MS and underscore the importance of establishing a psychiatric assessment in patients with MS from initial stages of the disease.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, anxiety-state scores, in combination with other biomarkers, also contributed to a prediction of neuropsychological performance in our patient cohort, highlighting the significant effect of anxiety symptoms on cognition in patients with MS. 32 These findings are not surprising given that high prevalence rates of psychiatric comorbidity 33 have been well documented in patients with MS and underscore the importance of establishing a psychiatric assessment in patients with MS from initial stages of the disease.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers have shown that anxiety harms verbal learning in MS patients, probably through interfering with attention and information processing speed. They have suggested that treatment of anxiety may improve cognitive function of MS patients (Vissicchio et al, 2019).…”
mentioning
confidence: 99%
“…Marck et al and Kos et al showed that there is a relationship between the sensitivity to anxiety and the QoL of people with MS [13,17]. Vissicchio et al showed that there is a relationship between anxiety and cognition in MS patients and anxiety has a significant effect on cognition [18]. Also, Rigikouteh et al showed that there is a relationship between the executive functions and QoL of people with MS [2].…”
Section: Discussionmentioning
confidence: 99%
“…In explaining these results, it can be stated that the goal of proper functioning of executive functions is to increase behaviors that are likely to lead to rewards from the patient, pleasure or sense of accomplishment (internal) or social attention (external) [6]. This increase in rewards first helps to improve the patient's positive emotional tolerance and ultimately improves intimate relationships [18]. The use of appropriate executive functions by reducing anxiety and sensitivity to anxiety leading to improving proper cognitive and emotional performance makes the MS patients able to solve the problem and increase their QoL [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation